Safety, effectiveness, and usefulness of higher-dose tablets of generic pirfenidone in patients with IPF: a nationwide observational study in South Korea - Kang, Jieun; Lee, Kwan Ho; Lee, Jae Ha; Jeong, Yi Yeong; Choi, Sun Mi; Kim, Ho Cheol; Park, Joo Hun; Lee, Hyun-Kyung; Yong, Suk Joong; Choi, Hye Sook; Kim, Hak Ryul; Jegal, Yangjin; et al. (Frontiers in Pharmacology, 2024)
Background: Pirfenidone is an antifibrotic medication approved for idiopathic pulmonary fibrosis (IPF). Fybro ® , a generic version of pirfenidone developed in South Korea, gained approval and is available in 200 mg and in higher-dose formulations of 400 and 600 mg. This real-world prospective cohort study investigated the safety and effectiveness of Fybro ® .Methods: A nationwide observational study was conducted in patients with IPF. Patients were followed up for 6 months, with a subset of patients being followed up for 12 months. Data on lung function and adverse events were collected. Patient adherence to fewer-pill (400 and/or 600 mg tablets) and multiple-pill (200 mg tablets) regimens were compared.Results: Of the 359 enrolled patients, 352 received pirfenidone (Fybro ® ) at least once and were included in the analysis. The mean age was 69.0 years and 82.4% of patients were male. The median treatment duration was 186.0 days. A total of 253 patients (71.9%) experienced adverse events, with decreased appetite being the most common (16.5%). The adjusted decline rates in lung function were -1.5% and -2.2% predicted per year for forced vital capacity and diffusing capacity, respectively. No significant differences were observed based on the pirfenidone dose.For a daily intake of 1200 or 1800 mg of pirfenidone, a significantly longer duration of drug administration was observed with the fewer-pill regimen than with multiple-pill regimen.The safety and effectiveness of Fybro ® observed in this real-world cohort study are consistent with previous studies. Using higher-strength tablets to reduce pill burden may improve medication adherence.